Evidence for interaction of the NLRP3 inflammasome and Bruton's tyrosine kinase in tumor-associated macrophages: implications for myeloid cell production of interleukin-1beta. (2nd November 2019) - Benner, Brooke; Scarberry, Luke; Stiff, Andrew; Duggan, Megan C.; Good, Logan; Lapurga, Gabriella; Butchar, Jonathan P.; Tridandapani, Susheela; Carson, William E.
ABSTRACT: An inflammatory microenvironment has been shown to play an important role in the growth and metastasis of tumors. The NLRP3 inflammasome is a multi-protein complex of the innate immune system that is responsible for the production of the potent inflammatory cytokine IL-1β. Tumor- associated macrophages (TAM) are an expanded population of immune cells found in the tumor microenvironment that can promote the initiation and metastasis of tumor cells. Their presence has been correlated with disease burden, highlighting the therapeutic potential of targeting this population. However, to date clinically relevant pharmacologic strategies to target TAM remain elusive. Here, we show that in vitro generated TAM harbor NLRP3 inflammasome components and produce IL-1β. Ibrutinib, an irreversible inhibitor of Bruton's tyrosine kinase (BTK), is in clinical use for the treatment of B- cell malignancies. We report that BTK is expressed by human in vitro generated TAM and murine macrophages and that it physically associates with the NLRP3 inflammasome. Furthermore, ibrutinib is able to inhibit BTK phosphorylation in TAM generated in vitro . Treatment of TAM with ibrutinib significantly impaired the ability of these cells to produce IL-1β. The present study provides evidence that BTK physically associates with the NLRP3 inflammasome and that inhibition of BTK with ibrutinib can impair the production of IL-1β by in vitro generated TAM. Thus, ibrutinib could potentially be of clinical use in abrogating inflammation-associated cancer progression and the immune-suppressive effects of myeloid cells within the tumor microenvironment.